Role of optimization algorithms based fuzzy controller in achieving induction motor performance enhancement - M. A. Hannan; Jamal Abd. Ali; M. S. Hossain Lipu; A. Mohamed; Pin Jern Ker; T. M. Indra Mahlia; M. Mansor; Aini Hussain; Kashem M. Muttaqi; Z. Y. Dong (Nature Communications, 2020)
Though optimization algorithms for fuzzy logic controller (FIC)-based three-phase induction motor (TIM) systems are attractive for improving efficiency, existing methods have limited search capability. Here, the authors report a quantum-inspired lightning search algorithm with enhanced performance.